2002
DOI: 10.1002/1438-9312(200211)104:11<745::aid-ejlt745>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Purification and deodorization of structured lipids by short path distillation

Abstract: Purification and deodorization of structured lipids by short path distillationPurification of structured lipids (SL), produced from lipase-catalyzed acidolysis of rapeseed oil and capric acid, and deodorization of randomized SL, produced from chemical randomization of fish oil and tricaprin, were studied in a bench-scale short path distillation (SPD). SL obtained from enzymatic acidolysis usually contain a large proportion of medium-chain and long-chain free fatty acids. Two SPD steps have been applied for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 16 publications
3
54
0
Order By: Relevance
“…Carbonyl off-flavour compounds are usually accompanied by free fatty acids, squalene, tocopherols and phytosterols, which are ordered according to the relative vapour pressure. Thus, deodorisation condensate is a rich source of valuable sterols and vitamin E derivatives (Čmolík & Pokorný 2000;Xu et al 2002). Isomerisation, oligomerisation, and numerous side reactions can occur during deodorisation.…”
supporting
confidence: 90%
“…Carbonyl off-flavour compounds are usually accompanied by free fatty acids, squalene, tocopherols and phytosterols, which are ordered according to the relative vapour pressure. Thus, deodorisation condensate is a rich source of valuable sterols and vitamin E derivatives (Čmolík & Pokorný 2000;Xu et al 2002). Isomerisation, oligomerisation, and numerous side reactions can occur during deodorisation.…”
supporting
confidence: 90%
“…The separation of the free fatty acids remaining after the reaction was conducted with short path distillation (KD6, UIC, Alzenau-Hoerstein, Germany) using a procedure described previously [11]. The distillation was conducted in two steps.…”
Section: Hmfs Production From Butterfatmentioning
confidence: 99%
“…The absence of tocopherols in the HMFS oils indicated that tocopherols were lost during the purification (pilot batch deodorization plus short path distillation) process of the enzyme modified oil. Previous studies had shown that substantial amounts of tocopherols are lost during purification of enzyme modified lipids if short path distillation is used as the purification method [4,11]. However, one of these studies showed that when batch deodorization was used the loss of tocopherol was much lower [11].…”
Section: Tocopherol Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Unreacted glycerol was separated by centrifugation and water washing. The residual oil was vacuum dried and FFA was removed by deodorization followed by short path distillation to produce 90 DAG 33 . Values are mean ± SD, n=3…”
Section: Resultsmentioning
confidence: 99%